Effect of age at cochlear implantation on speech and auditory performance - Alam, Mohammed Iftekharul; Asaduzzaman, A. K. M.; Hossain, Mohammad K.; Hossain, M. Belal; Mahmud, Tasnia (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Cochlear implants (CI) are currently widely accepted as treatment for patients with severe bilateral hearing loss. The outcomes of cochlear implantation among post lingual and crossover patients measuring surgical and functional outcomes and identifying areas which require further attention or improvement. Methods: This is retrospective clinical study was performed in a total of 80 children purposively screened from the patients who attended the outpatient clinic with complaints of hearing, speech or language impairment. The study group consisted those children who fit into the candidacy norms for cochlear implantation at the Department of ENT and Head-Neck Surgery, Combined Military Hospital, Dhaka from January 2017 to June 2019. Children with bilateral severe to profound sensori-neural hearing loss, age less than 5 years and prelingual deafness was included in this study. Results: Mean categorical auditory performance (CAP) and speech intelligibility rating (SIR) at 6 month and 12 month were statistically significant (p<0.05) compare with at 3 month. The mean post-operative CAP score was found significantly increased at 6, 12 and 24 month follow up age ≤3 years than >3 years (p<0.05). The mean post-operative SIR score was found significantly increased at 6, 12 and 24 month follow up in children age ≤3 years than >3 years (p<0.05). Conclusions: The majority of implanted have significantly gained auditory improvement as shown by the CAP and SIR scores in both group. Comparison between age group CAP and SIR score was significantly increased when children age <3 years than >3 years.